PCR-RFLP method for testing ASIP EXON 4 mutations in llamas - Daverio, Maria Silvana (2019)
The basic coat colors of mammals are determined by the relative proportion of two types of pigments, eumelanin and pheomelanin. The agouti signaling protein (ASIP) plays a crucial role in melanogenesis, by increasing the production of pheomelanin and decreasing the eumelanin synthesis by blocking the signaling pathway of the melanocortin 1 receptor (MC1R). In several species, loss of function mutations of the ASIP gene is responsible for the black coat color. The polymorphisms of ASIP exon 4, c.325_381del and c.292C> T, have been previously associated with eumelanic phenotypes in llamas (Daverio et al., 2016) and also in alpacas (Chandramohan et al., 2013). The objective of this work was to develop an alternative method to DNA sequencing for genotyping both polymorphisms. Fifty one llama DNA samples, including controls of known sequence were analyzed. PCR products spanning ASIP exon 4 were digested with the enzyme Bvel, that recognizes the c.292C>T mutation, followed by electrophoresis in 8% polyacrylamide gels to simultaneously detect the SNP and the deletion. Analysis of the band patterns presented complete concordance between DNA sequencing and PCR-RFLP genotypes. Genotyping results from the samples showed that all dark llamas (n=13) were homozygous for the deletion, homozygous for the c.292C> T polymorphism or heterozygous for both, while none of these combinations were observed in the pheomelanic animals here analyzed (n=20). The results of this work support the findings of previous studies and also show the usefulness of the PCR-RFLP technique as a relatively fast, simple and cost-effective method to determine the ASIP exon 4 variants in llamas.